Groundwater under strong influence of surface water – case study from Črneče (Northern Slovenia) - Brenčič, Mihael; Keršmanc, Teja (Geologija, 2016)
The article presents an analysis of the nine-year long data set of groundwater levels measurements in the influence area of the Drava River in Črneče in the southern Koroška (Carinthia - N Slovenia). Statistical analysis of the groundwater levels fluctuations, flow rates and stages of the Drava River were performed. It is followed by analysis of the interrelation between the groundwater level observations and mutual comparison between the groundwater level and river stages. Particular emphasis is placed on the analysis of the impact of extreme flood event on 05.11.2012 on groundwater levels, which caused catastrophic flooding throughout the whole Slovenian part of the Drava River Valley. With the help of groundwater level maps it is illustrated that in the hyporeic zone of the river intensive change in the distribution of groundwater flow field is undergoing. We are dealing with both the inflow of river water in the aquifer, as the outflow of groundwater into the river, and sometimes with the flow of groundwater which is parallel to the river bank.